1999
DOI: 10.1046/j.1523-1755.1999.00617.x
|View full text |Cite
|
Sign up to set email alerts
|

Bone mineral density and biochemical markers of bone turnover in patients with predialysis chronic renal failure

Abstract: Skeletal changes are initiated at an early stage of chronic renal failure, as estimated from reduced BMD and elevated levels of PTH and from the biochemical markers of both bone formation and bone resorption.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
173
4
5

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 274 publications
(192 citation statements)
references
References 46 publications
10
173
4
5
Order By: Relevance
“…BMD measurements, as measured by DXA, may be low, normal, or high in any form of ROD. Although CKD is highly co-prevalent with osteoporosis as measured by DXA (5), low DXA measurements may not signify osteoporosis in the setting of significant CKD (27,28). Standard therapies for osteoporosis often include calcium supplementation and bisphosphonates; both may be detrimental to patients with CKD.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…BMD measurements, as measured by DXA, may be low, normal, or high in any form of ROD. Although CKD is highly co-prevalent with osteoporosis as measured by DXA (5), low DXA measurements may not signify osteoporosis in the setting of significant CKD (27,28). Standard therapies for osteoporosis often include calcium supplementation and bisphosphonates; both may be detrimental to patients with CKD.…”
Section: Discussionmentioning
confidence: 99%
“…The referent category of kidney function in the categorical models was an eGFR Ͼ60 ml/min. We chose this level as the referent a priori because kidney disease complications typically begin after the GFR has decreased to Ͻ60% of normal, and kidney biopsy series have indicated that kidneyrelated bone disease is apparent at mild levels of kidney dysfunction (27,28).…”
Section: Statistical Analysesmentioning
confidence: 99%
“…The few prospective trials assessing the fracture prediction characteristics of DXA in CKD-mineral and bone disorder (CKD-MBD) patients are also inconsistent (9)(10)(11). Moreover, the spectrum of bone turnover and mineralization abnormalities that characterize renal osteodystrophy may be associated with low, normal, or high BMD (7,12,13). For these reasons, the 2009 Kidney Disease Improving Global Outcomes (KDIGO) Guidelines consensus statement on fracture risk assessment in CKD-MBD does not recommend using aBMD by DXA to screen patients for osteoporosis or to predict fracture risk (14).…”
mentioning
confidence: 99%
“…Although severe osteodystrophy is less common in earlier stages of CKD, elevated intact parathyroid hormone (iPTH) levels, considered one of the earliest markers of abnormal bone mineral metabolism in CKD, have been reported frequently in clinic-based studies of patients with renal insufficiency (3)(4)(5)(6)(7)(8)(9)(10). Also, even moderate reductions in renal function have been associated with significant increases in the risk of hip fracture (11,12).…”
mentioning
confidence: 99%